Body heat storage and physiological responses of periparturient Karan Fries and Sahiwal cows during summer and winter season - Vaidya, Mangesh M; Singh, Sohan Vir (Indian Journal of Animal Nutrition, 2019)
The experiment was conducted during summer and winter season on pregnant and lactating high and low producing Sahiwal and Karan Fries cows. Ten each of periparturient Karan Fries and Sahiwal cows were selected separately during summer and winter season from Livestock Research Centre of ICAR- National Dairy Research Institute Karnal (Haryana). Further, these animals were equally divided (five each) into high and low producing group during both the seasons on the basis of their earlier lactation milk yield. These animals were maintained on standard conditions of feeding and management followed at the institute farm. The physiological responses (RR, PR, Tre and Tskin) and climatic variables (Tdb, Twb, Tmax, Tmin,RH and THI) were recorded -45, -30, -15, 0, 15, 30, and 45 with respect to day of parturition and the heat storage of the animals were calculated. The physiological responses viz. rectal temperature, respiration rate, skin temperature, pulse rate and heat storage were significantly (P